Hardware implementation and performance evaluation of microcontroller-based 7-level inverter using POD-SPWM technique - Hajar Chadli; Sara Chadli; Mohamed Boutouba; Mohammed Saber; Abdelwahed Tahani (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Renewable energy sources are considered as inexhaustible sources for the very long-term, as they come from natural processes that are constantly replenished. However, there are a number of challenges facing renewable energy technology adoption, like the grid connecting problems. One of the main challenges relates to the grid connecting problem is the power quality issues for power converter, such as harmonics, voltage stability, and frequency fluctuation. Hence, the inverter remains the first element to be built because of its undeniable advantages in alternative continuous conversion. However, it has some disadvantages such as high component count and complex control method. This paper presents the design and implementation of a new 7-level inverter architecture with only six switches. This architecture requires fewer components compared to other 7-level inverter topologies therefore, the overall cost, control technique complexity, and conduction losses are highly reduced. A digital phase opposition disposition sinusoidal pulse width modulation (POD-SPWM) strategy using the Arduino is adopted to improve the performance of the proposed multilevel inverter (MLI) which leads to further reduction in total harmonic sistortion (THD). In this paper, the proposed inverter is tested using Proteus software and Matlab Simulink. Finally, a laboratory setup of the proposed inverter was built to validate its workability by the experimental results.